Conditions d'apparition d'une embryogénèse somatique sur des cals issus de la culture de tissus foliaires du chêne vert (Quercus ilex) - Féraud-Keller, C.; ESPAGNAC, H. (Canadian Journal of Botany, 1989)
The proliferation of parenchymatous foliar tissue of Quercus ilex was obtained from current year leaves taken from old trees and cultivated in vitro on modified Murashige and Skoog's medium supplemented with benzylaminopurine (4 mg ∙ L−1) and naphthyl acetic acid (0.5 mg ∙ L−1). Only the fragments cultured in October reacted. The neoformations only appeared on calluses that had not been subcultured for 7 months. Primary nodules arising on these calluses were removed and subcultured on the same medium either in the dark or in the light. In the dark only, they produced secondary nodules, which were the source of somatic embryos both in light and dark. Presently, they seem to regulate their structure in the dark but they do not develop in a way that leads to germination.
doi: 10.1139/b89-139doi: 10.1139/b89-139The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: Callus; Quercus ilex; tissue culture